Structural Motion Engineering - Connor, Jerome; Laflamme, Simon (Springer International Publishing : Imprint: Springer, 2014)
This innovative volume provides a systematic treatment of the basic concepts and computational procedures for structural motion design and engineering for civil installations. The authors illustrate the application of motion control to a wide spectrum of buildings through many examples. Topics covered include optimal stiffness distributions for building-type structures, the role of damping in controlling motion, tuned mass dampers, base isolation systems, linear control, and nonlinear control. The book's primary objective is the satisfaction of motion-related design requirements, such as restrictions on displacement and acceleration. The book is ideal for practicing engineers and graduate students. This book also: ·         Broadens practitioners' understanding of structural motion control, the enabling technology for motion-based design ·         Provides readers the tools to satisfy requirements of modern, ultra-high strength materials that lack corresponding stiffness, where the motion requirements control the design ·         Equips engineers and designers to adapt to more-excitable, contemporary structures that experience more structural motion under service loading ·         Explains the severe design constraints attending structures such as micro-device and semiconductor manufacturing centers in which the environment must be virtually motion free ·         Illustrates motion-based energy absorption mechanisms as a cost-effective alternative over inelastic deformation to dissipate energy and control structural response ·         Features nearly 400 figures.